Pengaruh Return On Asset, Return On Equity, Net Profit Margin, Dan Debt To Equity Ratio Terhadap Harga Saham Pada Perusahaan Subsektor Properti Yang Terdaftar Di Bursa Efek Indonesia - Gina Lorensa; Diana Sari (CV. ITTC INDONESIA, 2026)
Stock price is the price of a stock that is traded. This study aims to find out and analyze the effect of Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER) on Share Price individually and simultaneously in property sub-sector companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sampling method used in this study used purposive sampling technique. The sample used is a property sub-sector company listed on the Indonesia Stock Exchange for the 2019-2023 period. So that the sample obtained was 6 companies or n = 30. The data used is secondary data, namely annual financial reports and company stock prices. The analysis technique used in this research is multiple linear regression analysis. The tool used is IBM SPSS version 26 software. The results of this study indicate that the Net Profit Margin (NPM) variable affects the stock price. While the variables Return On Asset (ROA), Return On Equity (ROE), and Debt to Equity Ratio (DER) have no effect on stock prices. Simultaneously, the variables Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM), Debt to Equity Ratio (DER) affect stock prices.